THE EFFECT OF ADMINISTRATION OF FE TABLETS USING THE CERIA APPLICATION ON INCREASING HB LEVELS IN ADOLESCENT WOMEN AT MTs NEGERI 4 TASIKMALAYA - Anwar, Rivqoh Saidah; Tajmiati, Atit; Rismawati, Sariestya (Asian Research Midwifery and Basic Science Journal, 2024)
The prevalence of anemia in adolescent girls is around 30%, in fact the results of a study in West Java show that the prevalence rate of anemia in adolescent girls is above 50%. Based on data in Tasikmalaya City in 2022, it is known that the prevalence of anemia in adolescent girls aged 12-19 years is 44.51%. One of the programs for providing Fe tablets is by utilizing an existing application, namely Ceria. This study aims to determine and analyze the effect of administering Fe tablets using the Ceria application on increasing Hb levels in adolescents. This type of research is a pre-experimental design research with one group pretest posttest design. The population in this study was all 261 young women at MTs Negeri 4 Tasikmalaya for the 2023-2024 academic year. The sample used in this research was 33 people using purposive sampling technique. The data analysis used was the Wilcoxon test. The research results showed that all young women consumed Fe tablets given in the complete category and used the Ceria application, namely 33 people (100%). The Hb levels of female teenagers at MTs Negeri 4 Tasikmalaya before consuming Fe tablets using the Ceria application were in the anemia category (100%) and after consuming Fe tablets using the Ceria application, the majority were in the non-anemia category (78.8%). Providing Fe tablets using the Ceria application has an effect on increasing Hb levels in young women at MTs Negeri 4 Tasikmalaya in 2023, this is proven by the Wilcoxon (Z) test value of -5.013 and a ρvalue of 0.000. Therefore, the Ceria application can be used as an evaluation of the program for providing Blood Supplement Tablets (TTD) to young women.